Response of soil microbial community structure to temperature and nitrogen fertilizer in three different provenances of Pennisetum alopecuroides - Deng, Niandong; Nian, Lili; Zhang, Shuolun; Liang, Yixuan; Shang, Huiying; Li, Yang; Mao, Zhuxin (Frontiers in Microbiology, 2024)
Soil microorganisms are key indicators of soil health, and it is crucial to investigate the structure and interactions of soil microbial communities among three different provenances of Pennisetum alopecuroides under varying nitrogen fertilizer and temperature levels in Northwest China. This study aims to provide theoretical support for the sustainable use of artificial grassland in this region.Employing a two-factor pot-control experiment with three nitrogen fertilizer treatments and three temperature treatments, a total of all treatments was utilized to examine the composition and abundance of soil microbial communities associated with Pennisetum alopecuroides using high-throughput sequencing, PCR technology, and molecular ecological network analysis. The results revealed that Proteobacteria was the dominant bacterial phylum while Ascomycota was the dominant fungal phylum in the soil samples from three provenances of Pennisetum. Specifically, Proteobacteria exhibited higher abundance in the N3T2 treatment compared to other treatments under N3T2 (25-30 ℃, 3g/pot) treatment conditions in Shaanxi and Gansu provinces; similarly, Proteobacteria was more abundant in the N1T2 (25-30 ℃, 1g/pot) treatment in Inner Mongolia under N1T2. Moreover, Ascomycota displayed higher abundance than other treatments in both Inner Mongolia and Gansu provinces.Additionally, Pennisetum Ascomycota demonstrated greater prevalence under (25-30 ℃, 3g/pot) treatment compared to other treatments; furthermore, Shaanxi's Pennisetum Ascomycota exhibited increased prevalence under N3T1 (18-23 ℃, 3g/pot) treatment compared to other treatments. The richness and diversity of soil microbial communities were significantly influenced by nitrogen fertilizer and temperature changes, leading to notable alterations in their structure. Molecular ecological network analyses revealed strong collaborative relationships among microbial species in Shaanxi Pennisetum and Inner Mongolia Pennisetum under high nitrogen and high temperature treatments, while competitive relationships were observed among microbial species in Gansu Pennisetum under similar conditions. Redundancy analysis indicated that soil pH, total potassium, and total phosphorus were the primary environmental factors influencing microorganisms. In summary, this study offers a theoretical foundation for assessing the sustainable utilization of Pennisetum Response of Soil Microbial Community to Temperature and Nitrogen Fertilizer artificial grasslands in Northwest China by investigating the shifts in soil microbial communities and the driving factors under varying nitrogen fertilizer and temperature levels.